Textual Understanding of The Prophet’s Hadith: (Study of the Understanding of Ahmad Hassan’s Traditions) - Hasan, Zakiyah; Safri, Edi; Hakim, Luqmanul (Journal of Hadith Studies, 2019)
This article examines the research of Ahmad ‘Ubaydi Hasbillah, which identifies Ahmad Hassan as a prominent figure in textual hadith studies. In his book Nalar Tekstual Ahli Hadis: Akar Formula Kultur Moderat Berbasis Tekstualisme, ‘Ubaydi asserts that Ahmad Hassan belonged to a group known for its strong textualist approach, displaying remarkable diligence in hadith studies. This article uses Ahmad Ubaydi Hasbillah’s research as a framework to explore Ahmad Hassan’s understanding of various hadiths. Specific topics discussed include the hadiths on licking dogs, reciting al-Fatiha in congregational prayers, touching the Qur'an, drawing or cheap images, and the use of sutrah in prayer. As an Indonesian scholar, Hassan was known for his courage in opposing views not grounded in the primary sources of Islamic law—namely, the Qur'an and Hadith. His understanding of these hadiths has occasionally been labeled as radical due to his firm stance. Although Hassan is primarily associated with a textual approach, he also integrated contextual analysis in certain instances.